Ijab Qabul Perkawinan Yang Diwakilkan Berdasarkan Hukum Islam Dihubungkan Dengan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Salidja, Suhaendi; Anjani, Aan (Universitas Wiralodra, 2016)
In fact, society is often ignore Meaning of Marriage is not paying attention to the norms and rules of life in society. The lack of understanding in the sociaty it make a processes and procedures in the marriage increasingly forgotten. One of those is marriage without bride when said ijab qobul and it is represented by the other people. It is lawful According to the positive law in Indonesia as explained on Islamic law, as for feedback society Regarding the marriage those that 'especiallay the ordinary people still are not knowing and so they assume that marriage is not legitimate.